Hanpen Fish Cake, Rough Flathead (Grammoplites scaber) Diversification Product - Lubis, Novita Sari; Diana, Ayu; Yusfiani, Marnida (Talenta Publisher, 2020)
ABSTRACT Rough flathead (Grammoplites scaber) is a non-economical and white-fleshed fish. It's suitable for fish-based processing products. Hanpen is one of the Japanese fish cake. Diversification of surimi-based Rough flathead becomes Hanpen. This research studied the consumer acceptance and chemical composition of Hanpen Rough flathead. The experimental methods are used in this research with 3 treatments and Deuteronomy, the addition of surimi Rough flathead A1 = 100 g, A2 = 150 g, and A3 = 200 g. The randomized block data, ANOVA, was performed to analyze the data. The results showed that Hanpen Rough flathead product that can be accepted by panelists is A2 treatment, which scores 7,28 at like level specification. The addition of surimi Rough flathead had a significant effect (p<0,05) on organoleptic test parameters (appearance, aroma, taste, and texture) and proximate tests (crude protein, crude fat, water content, ash content, and carbohydrate) to Hanpen. The highest value of proximate test for three treatments were crude protein = A1 (5,36); carbohydrate = A1 (11,36); crude fat = A2 (0,39); water content = A3 (83,67); dan ash content = A2 (2,84). References Agustin, T. I. (2012). Mutu fisk dan Mikrostruktur Kamaboko Ikan Kurisi ( Nemipterus nematophorus ) dengan Physical and Microstructure Quality of Kamaboko Kurisi Fish. JPHPI, Masyarakat Pengolahan Hasil Perikanan Indonesia, 15(1), 18–26. Bozova, B., & Centinkaya, S. (2019). Surimi and surimi products. 2nd International Symposium on Limnology and Freshwater Fiheries. BPS. (2019). Produksi Perikanan menurut Asal Tangkapan di Kota Tanjungbalai 2010 - 2017. Retrieved March 23, 2020, from https://tanjungbalaikota.bps.go.id/dynamictable/2017/07/12/110/produksi-perikanan-menurut-asal-tangkapan-di-kota-tanjungbalai-ton-2010-2017.html Damanik, M. R. S., Sriadhi, Habibi, M. R., & Harefa, M. S. (2018). Diversifikasi Pengolahan Ikan sebagai Upaya Peningkatan Ekonomi Masyarakat Nelayan Desa Bagan Serdang Kecamatan Pantai Labu Kabupaten Deli Serdang. Jurnal Pengabdian Kepada Masyarakat, 23(4), 455–459. Diana, A., & Lubis, A. F. (2018). Peningkatan Potensi Ikan Baji - Baji ( Grammoplites scaber ) Dan Proporsi Bagian Tubuh Sebagai Sumber Bahan Baku. AGRINTECH: Jurnal Teknologi Pangan Dan Hasil Pertanian, 2(1), 14–22. Ilza, M., & Siregar, Y. I. (2015). Sosialisasi penambahan minyak perut ikan jambal siam dan minyak ikan kerapu pada bubur bayi untuk memenuhi standar omega 3 dan omega 6. Jphpi, 18, 262–275. https://doi.org/10.17844/jphpi.2015.18.3.262 Jia, R., Katano, T., Yoshimoto, Y., Gao, Y., Nakazawa, N., Osako, K., & Okazaki, E. (2020). Effect of small granules in potato starch and wheat starch on quality changes of direct heated surimi gels after freezing. Food Hydrocolloids, 104(February), 105732. https://doi.org/10.1016/j.foodhyd.2020.105732 Karsa, A. (2004). Kebiasaan Makanan Ikan Baji-baji (Grammoplites scaber (Linnaeus, 1758)) di Perairan Mayangan, Subang, Jawa Barat. Institut Pertanian Bogor. Kim, S. K. (2013). Seafood processing by-products: Trends and applications. Seafood Processing By-Products: Trends and Applications, 9781461495(March 2014), 1–597. https://doi.org/10.1007/978-1-4614-9590-1 Kobayashi, Y., Huge, J., Imamura, S., & Hamada-Sato, N. (2016). Study of the cross-reactivity of fish allergens based on a questionnaire and blood testing. Allergology International, 65(3), 272–279. https://doi.org/10.1016/j.alit.2016.01.002 Kwon, Y.-M., & Lee, J.-S. (2013). A Study on the Quality Characteristics of Fish Cakes Containing Rice Flour. Korean Journal of Human Ecology, 22(1), 189–200. Laksono, U. T., Suprihatin, S., Nurhayati, T., & Romli, M. (2019). Enhancement of Textural Quality From Daggertooth Pike Conger Fish Surimi with Sodium Tripolyphosphate and Transglutaminase Activator. Jurnal Pengolahan Hasil Perikanan Indonesia, 22(2), 198–208. https://doi.org/10.17844/jphpi.v22i2.27373 Motamedi, M., Teimori, A., Amiri, V., & Hesni, M. A. (2020). Characterization of age-dependent variability in the flank scales of two scorpaeniformes fishes by applying light and scanning electron microscopy imaging. Micron, 128(September 2019), 102778. https://doi.org/10.1016/j.micron.2019.102778 Nurhadi, B., & Nurhasanah, S. (2010). Sifat Fisik Bahan Pangan. Bandung: Widya Padjajaran. Radityo, C., Darmanto, Y., & Romadhon, R. (2014). Pengaruh Penambahan Egg White Powder Dengan Konsentrasi 3% Terhadap Kemampuan Pembentukan Gel Surimi Dari Berbagai Jenis Ikan. Jurnal Pengolahan Dan Bioteknologi Hasil Perikanan, 3(4), 1–9. Rijal, M. (2017). Diversifikasi Produk Olahan Ikan Bagi Ibu-Ibu Nelayan di Dusun Mamua Kabupaten Maluku Tengah. Jurnal Biology Science & Education, 6(2), 159–170. Satam, S. B., Sharangdhar, S. T., Sharangdhar, M. T., Sajid, I. K., & Sonawane, U. D. (2004). Surimi : The